Climate information training of trainers manual and guide: For Extension Officers on Interpretation and Use of Agrometeorological Information and Products for Climate-resilient Agriculture and Food Security - United Republic of Tanzania (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Tanzania, just like much of the globe, has continued to experience extreme weather events due to climate variability and change. Climate change has led to an increase in frequency and magnitude of extreme weather and climate-related events including floods, droughts, high incidences of strong winds and high temperature. As a result, reduced groundwater recharge, increased pest incidences, and disease epidemics have become a bigger challenge suppressing and distorting efforts to improve productivity in the agriculture sector. This means, national food security and development initiatives can be affected to the extent of jeopardising Tanzania’s efforts towards achieving the Sustainable Development Goals (SDGs), specifically Goal 2 on Zero Hunger.